PENTINGNYA SISTEM INFORMASI AKUNTANSI YANG HANDAL TERHADAP BENCANA PADA SEKTOR PEMERINTAHAN - Fifi Yusmita; Evayani Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
Many organizations are starting to realize the importance of having a robust and reliable accounting information system (AIS), but many hesitate to apply this system before a disaster occurs. Therefore, this study aims to provide insight into the importance of a robust and reliable AIS from the stakeholder's perceptions. A qualitative method was the method used to explore the issues in this study. Sampling consists of 7 key informants who have qualified capability and knowledge in the government sector and AIS sector. The result showed that having a reliable AIS within a government organization sector is very important to be adopted because of the benefits offered from its system, as well as directly minimize the negative impact of unpredictable disasters.